UPSTREAM AND DOWNSTREAM UNIFICATION IN SOUTHEAST ASIA'S FIRST ISLAMIC POLITY: THE CHANGING SENSE OF COMMUNITY IN THE FIFTEENTH CENTURY HIKAYAT RAJA-RAJA PASAI COURT CHRONICLE - Hall, Kenneth (Journal of the economic and social history of the Orient, 2001)
Abstract This study on the thirteenth and fourteenth century emergence of Southeast Asia's earliest Islamic state examines how the fifteenth century Hikayat Raja-Raja Pasai court chronicle can be used to understand the Samudra-Pasai port-polity and its legitimation. The local pre-Islamic north Sumatra order is first portrayed in the Hikayat, which highlights the sovereign's mythical attributes. Indian Ocean commercial and diplomatic channels then provided access to imported textiles, which became the centerpiece of the monarch's ritualized redistributions, as well as the opportunity to enter membership in the community of Islam. Samudra-Pasai's newly converted sultans successfully linked disparate upstream and downstream population clusters under the leadership of their port-centered court, in ways that were not only consistent with local beliefs, but also appropriate to an Islamic society. Cette étude, sur l'émergence du premier état islamique en Asie du sud-est aux treisième et quatorzième siècles, considère comment la chronique de la cour de Hikayat Raja-Raja Pasai, datant du quinzième siècle, peut être utilisée pour comprendre le port-régime de Samudra-Pasai et sa légitimation. L'ordre local et pré-islamique de Sumatra du nord est représenté dans le Hikayat, un texte qui souligne les attributs mythiques du souverain. En particulier, le réseau commercial et diplomatique, centré sur l'océan indien, a permis l'accès aux textiles importés, qui sont devenus la pièce maîtresse du système monarchique de rédistribution rituelle, et l'occasion d'entrer comme membre dans la communauté d'islam. Les souverains de Samudra-Pasai a relié avec succès les populations disparates en amont and en aval de la rivière sous la direction de la cour, centré sur le port, par les moyens qui conforment non seulement aux croyances locales mais aussi qui conviennent à une société islamique.